First Record of the Family Potamocoridae (Hemiptera: Heteroptera) in Costa Rica and of Coleopterocoris Hungerford, 1942 in Central America - Herrera, Federico; Springer, Monika (Zootaxa, 2012)
The Neotropical family Potamocoridae includes nine species in the genera Coleopterocoris Hungerford, 1942 and Potamocoris Hungerford, 1941. The biology of the family is barely known and most of the species mentioned in the literature have been collected with light-traps. Coleopterocoris has been reported only from Brazil and is represented by five described species, whereas Potamocoris has a more extensive known distribution, with one species recorded from Honduras and Mexico, and three from Suriname, Peru, and Paraguay (Hungerford 1941; La Rivers 1950; La Rivers 1969; Polhemus & Polhemus 1983; Van Doesburg 1984; Longo et al. 2005)